Ophiostomatoid fungi isolated from three different pine species in Argentinian Patagonia - de Errasti, Andres (2018)
Pine plantations in Argentinian Patagonia cover ca. 95,000 ha in Chubut, Río Negro and Neuquén provinces. Exotic bark beetles (Orthotomicus laricis, Hylastes ater and Hylurgus ligniperda) commonly occur in freshly cut logs, stumps and slash. These beetles are vectors of “ophiostomatoid” fungi which include primary tree pathogens as well as important agents of blue stain. The aim of this study was to identify these beetle-associated fungi. Sawing mills and pine plantations were surveyed three consecutive years. Fungal isolates from stained logs, processed wood and insect galleries were identified based on morphological and DNA sequence comparisons of ITS and β-tubulin gene regions. Two Grosmannia, one Graphilbum and three Ophiostoma species were identified. Ophiostoma piliferum and O. peregrinum sp. nov. were the most frequently isolated taxa. O. peregrinum occurred in all provinces, colonizing different conifer species and, interestingly, also the native broadleaved species Nothofagus dombeyi. Pine plantation forestry in southern South America includes Argentina, Brazil, Chile, Paraguay and Uruguay. Emerging data from Argentina, Chile and Uruguay revealed some coincidences between these countries, but also several differences, probably, as a result of multiple introduction events.